The level of school bullying with middle school stage pupils - A field study at middle schools in Algiers - Abib, Ghania; Lallouche, Saliha (Journal of Educational and Psychological Sciences, 2023)
This study aims at revealing the level of school bullying with middle school stage pupils and looking for the differences’ significance in school bullying, which refers to classroom variable. For achieving the study objectives, the descriptive method has been applied on a sample of 122 middle school stage pupils in Algiers. School bullying scale has been applied, after checking its reliability and consistency. The collected data has been analyzed through using the Statistical Pack for Social Sciences (SPSS), since it contains statistical ways. The study has concluded with the fact that the level of school bullying with middle school stage pupils is low, and there’re no differences with statistical significance among the middle school stage pupils’ averages on school bullying scale, due to classroom variable. The research recommends helping the pupils to get rid of their negative energies through practicing sport and different artistic and scientific activities regularly and periodically at schools, which helps the pupils’ social relationships’ development and the acquisition of social skills as well. This would help eliminating the school bullying phenomenon and raising the pupils’ morale through the positive interaction at school.